Pelatihan Pemanfaatan Kecerdasan Buatan (AI) untuk Pengembangan Media Pembelajaran bagi Guru Sekolah Dasar - Abdulah; Ulyma Tahara Arisandi; Azka 'Afifah; Hairul; Rahma Aini; Ravinda Aris Munandar (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2026)
The use of artificial intelligence (AI) in education has significant potential to improve the quality of learning, particularly in the development of creative and innovative instructional media. However, many elementary school teachers still face limitations in knowledge and skills related to the pedagogical use of AI. Therefore, this community service activity aimed to enhance the competence of teachers at SD Negeri 18 Pangkalpinang in developing AI-based learning media that align with the characteristics of elementary school students. The activity was conducted on December 9, 2025, involving all teachers through training sessions, hands-on practice, mentoring, and reflection. The success of the program was measured through observations, interviews, and assessment of the learning media products developed by the teachers. The results indicate an improvement in teachers’ understanding and skills in selecting and utilizing AI applications, as well as increased creativity in producing more varied and relevant learning media aligned with instructional objectives. In addition, teachers demonstrated a more positive attitude and greater openness toward the use of technology in learning. This activity highlights the importance of practical and contextual AI utilization training in supporting learning transformation in elementary schools and contributing to sustainable improvement in educational quality.